2015
DOI: 10.1007/s00383-015-3740-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in the incidence of anorectal malformations between a first- and third-world referral center

Abstract: Purpose Aim of study was to evaluate the differences in incidence and presentation of anorectal malformations (ARMs) between selected Pediatric Surgery Divisions in the Republic of South Africa (ZAR) and Italy. Methods A retrospective cohort study involved analysis of clinical records of patients with ARM born between 2005 and 2012. Type of ARM, maternal age, birth weight, gestational age, presence of associated anomalies and delayed diagnosis were analyzed. Results 335 patients were included in this study. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
3
8
0
1
Order By: Relevance
“…Associated congenital malformation accounted for 44% (44/99) of patients. The large number of associated congenital malformation seen in this study is similar with the studies conducted in other studies (2,6,7,13). Genitourinary malformations are the dominant associated lesions detected in this study which is 31% (31/99) and it is in line with the studies done somewhere else (2, 11-13).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Associated congenital malformation accounted for 44% (44/99) of patients. The large number of associated congenital malformation seen in this study is similar with the studies conducted in other studies (2,6,7,13). Genitourinary malformations are the dominant associated lesions detected in this study which is 31% (31/99) and it is in line with the studies done somewhere else (2, 11-13).…”
Section: Discussionsupporting
confidence: 81%
“…This finding is similar to the study done in Italy where 54% of their patients are females and to the proportion noticed from our institute 36 years back, 53%:47% respectively (7,8). However, study done in South Africa indicated that the ratio of male to female patients is grossly equal (4,6,9). There was a delay in presentation in 94 % of the cases.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Average maternal age in ZAR group and Italian group was, respectively, 28 and 34 years (p = 0.0001). [10] Ciongradi et al (2016) did retrospective analysis of 146 patients with ARM in which mothers age ranged from 16 to 42 years old, with a mean age of 21.3 ± 2.3 years old. [11] In the present study age of mothers ranged from 19 to 36 years with a mean age of 25.04±4.10 years.…”
Section: Discussionmentioning
confidence: 99%
“…This traditional approach is especially applicable in LMICs, where patients often present late with established obstruction of the gastrointestinal tract, systemic sepsis and dehydration. [4][5][6][7] Some lesions are amenable to a primary PSARP without formation of a colostomy if the anatomical defect is favourable, the child is clinically stable and has no associated life-threatening congenital anomalies, and there is no gross abdominal distension. [8] In the paediatric population, intra-abdominal surgery is associated with a 20% surgical site infection rate and an 11% anastomotic leak rate.…”
Section: Researchmentioning
confidence: 99%